2017
DOI: 10.1902/jop.2017.160629
|View full text |Cite
|
Sign up to set email alerts
|

Modifications in Human Oral Fibroblast Ultrastructure, Collagen Production, and Lysosomal Compartment in Response to Electronic Cigarette Fluids

Abstract: E-cigarette fluids (with and without nicotine) trigger molecular and morphologic responses in oral fibroblasts, raising concerns about their role in the pathogenesis of oral diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…In the present study, we observed that chronic nicotine exposure enhanced autophagy biomarkers (such as LC3II, p62, Beclin 1, and Atg 5) protein abundance in cardiac tissues. Consistent with our observation, other studies have shown that nicotine exposure increases autophagy activation in human fibroblast cells [31], human cancer colon cells [32], and bronchial epithelial cells [13]. These findings suggest that nicotine is one of the key activators of autophagy.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we observed that chronic nicotine exposure enhanced autophagy biomarkers (such as LC3II, p62, Beclin 1, and Atg 5) protein abundance in cardiac tissues. Consistent with our observation, other studies have shown that nicotine exposure increases autophagy activation in human fibroblast cells [31], human cancer colon cells [32], and bronchial epithelial cells [13]. These findings suggest that nicotine is one of the key activators of autophagy.…”
Section: Discussionsupporting
confidence: 93%
“…The nicotine‐containing treatment in our collagen type I RNA and protein experiments had a concentration of 620 μ m (0.1 mg/mL), which falls in between these previous reports, although it is below the 1 m m concentration reported to result in downregulation. Consistent with the biphasic nature of nicotine, when human oral fibroblasts are exposed to unvaped e‐liquid containing 6.2 m m nicotine for 24 hours there is a decrease in collagen type I protein (Sancilio et al, ). In addition to nicotine, the flavorings alone may alter osteoblast gene expression.…”
Section: Discussionmentioning
confidence: 85%
“…Results from recent studies showed that cigarette smoke could induce the autophagy in cells from periodontal tissues (Du et al, ; Kim et al, ; Moga et al, ; Sancilio et al, ; Table ). Moga et al reported that nicotine could induce the presence of autophagosomes in mesenchymal stem cells from human periodontium (including gingival ligament stem cells, periodontal ligament stem cells, gingival tissue stem cells, and alveolar bone stem cells) at intermediate doses (0.622–3.112 μM; Moga et al, ).…”
Section: Autophagy and Cigarette Smokementioning
confidence: 99%
“…Sancilio et al found that cigarette fluids, no matter with or without nicotine, could induce the presence of autophagic vesicles, but the expression of LC3 and the release of collagen could not be regulated by cigarette fluid without nicotine in HGFs. It was suggested that the cigarette without nicotine might regulate autophagy via cellular morphologic response (Sancilio et al, ).…”
Section: Autophagy and Cigarette Smokementioning
confidence: 99%
See 1 more Smart Citation